2012
DOI: 10.1002/jbmr.1826
|View full text |Cite
|
Sign up to set email alerts
|

Loss of equilibrative nucleoside transporter 1 in mice leads to progressive ectopic mineralization of spinal tissues resembling diffuse idiopathic skeletal hyperostosis in humans

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is a noninflammatory spondyloarthropathy, characterized by ectopic calcification of spinal tissues. Symptoms include spine pain and stiffness, and in severe cases dysphagia and spinal cord compression. The etiology of DISH is unknown and there are no specific treatments. Recent studies have suggested a role for purine metabolism in the regulation of biomineralization. Equilibrative nucleoside transporter 1 (ENT1) transfers hydrophilic nucleosides, such as adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 65 publications
(94 reference statements)
7
93
1
Order By: Relevance
“…by guest www.bloodjournal.org From support this hypothesis. 13,14 The precise role of ENT1 in bone homeostasis remains to be established in mice and humans, but it is most likely linked to its ability to transport adenosine, which has emerged as a key regulator of bone metabolism. 15 In fact, other genes of the adenosine pathway have been found to be responsible for calcification disorders.…”
Section: Resultsmentioning
confidence: 99%
“…by guest www.bloodjournal.org From support this hypothesis. 13,14 The precise role of ENT1 in bone homeostasis remains to be established in mice and humans, but it is most likely linked to its ability to transport adenosine, which has emerged as a key regulator of bone metabolism. 15 In fact, other genes of the adenosine pathway have been found to be responsible for calcification disorders.…”
Section: Resultsmentioning
confidence: 99%
“…30 This mouse was developed as a model for diffuse idiopathic skeletal hyperostosis (DISH), a non-inflammatory spondyloarthropathy characterized by ectopic mineralization of spinal tissues. This mouse model was generated through targeted deletion of exons 2-4 of the gene encoding ENT1.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to our findings on Nt5e ¡/¡ mice, the Ent1 -/-mice showed no evidence of mineralization in blood vessels, indicating specificity of the mineralization process in these mice for the axial skeleton. 30 Collectively, the mouse models of ectopic mineralization, including those with CD73 and ENT1 deficiency, attest to the presence of a complex pro-mineralization/anti-mineralization network that under physiologic homeostatic conditions prevents ectopic mineralization of soft connective tissues. 12 Alterations in the components of this network, such as altered ratio of P i /PP i and the adenosine concentration, can result in mineralization pathways with phenotypic tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (72) developed the first reported ENT1-null mouse and demonstrated that it maintained normal reproductive behavior, had no gross anatomical abnormalities, and survival rates were similar to wild-type mice, although, bodyweight was significantly less than wild-type littermates (7274). Several studies have utilized ENT1 null mice (20, 7277) and found that these mice possess elevated circulating adenosine and thymidine levels in the plasma, reduced cellular uptake of adenosine (20, 73, 75), aberrant bone density (73, 74), dysregulation of the calcification of soft tissues associated with the enthesis regions of the vertebral column and sternum (73), increased resistance to oxidative stress (76), deficit in locomotor activity and motor coordination (74, 77), increased voluntary ethanol self-seeking behaviors associated with increased resistance to acute ethanol intoxication and reduced aversive effects of ethanol (72, 77), and that the absence of ENT1 is associated with reduced anxiety-like behavior in mice (78). …”
Section: Functional Characterization Of Mammalian Ent Proteinsmentioning
confidence: 99%